Host vs. pathogen evolutionary arms race: Effects of exposure history on individual response to a genetically diverse pathogen - Walsh, Daniel P.; Felts, Brandi L.; Cassirer, E. Frances; Besser, Thomas E.; Jenks, Jonathan A. (Frontiers in Ecology and Evolution, 2023)
Individual response to pathogen exposure emerges from dynamic interactions between competing evolutionary processes within the host and pathogen. The host’s adaptive immune system recognizes pathogens and mounts a defensive response. Pathogens have evolved strategies to overcome adaptive immune defenses including maintaining high genetic diversity through rapid evolution. The outcomes of this evolutionary warfare determine the success of pathogen invasion of the host. We had the unique opportunity to examine the variation in impacts of pathogen invasion on captive bighorn sheep (Ovis canadensis) with differing histories of exposure to genetically diverse strains of Mycoplasma ovipneumoniae (Movi) during an epizootic dominated by a single strain. We monitored clinical signs of disease and sampled animals and their environment to detect spread of Movi among 37 bighorn sheep separated into nine pens based on known exposure histories. We documented Movi transmission within and across pens and we detected Movi DNA in air, water, and invertebrate samples. We found that higher levels of antibody to Movi prior to the epizootic were associated with a lower likelihood of presenting clinical signs of pneumonia. However, higher antibody levels in symptomatic individuals were associated with more severe progressive disease, increased probability and speed of pneumonia-induced mortality, and reduced likelihood of returning to a healthy state. Bighorn sheep with previous exposure to a strain other than the predominant epizootic strain were more likely to recover. Our results suggest that Movi-strain variability was sufficient to overwhelm the adaptive host immunological defenses under the conditions of this study. Therefore, in free-ranging herds past exposure is likely insufficient to protect bighorn sheep from infection by new Movi strains, although it may influence the progression of disease and recovery within the herd.